Intelligence based techniques for assessment and control of vehicle-to-grid (V2G) in power system - Ahmad, Mohamad Redzuan; Ishak, Ruhaizad; Aliman, Omar (2020)
Due to growing global interest towards alternative energy resources and environmental concerns, Electric Vehicle (EVs) has proved to be the best alternative and are fast developing in recent 21st century. An increase in EV integration with an electric grid raises concerns about the health of the electrical grid due to increase of charging load. Electric vehicles have the potential to play the Vehicle-to-Grid (V2G) role as the vehicle becomes an asset in a smart grid with bi-directional chargers. V2G which achieves bidirectional power flow between the Electric Vehicle and power grid, will bring new applications for optimal operation of power systems. One of the most important application is to provide frequency regulation service. Moreover, it has been calculated that 92% of the total vehicles stay parked even during the peak hours or about 20 hours a day for the vehicle remain static. This increase the chance for the vehicle being available for V2G. This paper evaluates the capability of the Vehicle-to-Grid to provide ancillary service for frequency regulation. In addition, there are 3 main case studies that have been conducted to evaluate the impact of V2G as frequency regulator in a micro grid area. These case studies are the possible event that might be occurred in micro grid system and cause disturbance of the system frequency. The first case study is to investigates the impact of sudden increase of residential peak load due to the Plug-in Hybrid Vehicle (PHEV) charging load to the system frequency of the micro grid. The PHEV Charging Load Profile (PCLP) was analysed based on real the data from National Household Travel Survey 2017. The second case study is to implement the V2G system when there are 3 power system disturbances occur in Micro Grid system. These disturbances will definitely disturb the normal system frequency of the micro grid. The third case study is to evaluate the frequency regulation when there was partial shading occurred during noon that effect the solar panel output power. In this project, the simulation of Vehicle-to-grid system was simulated using model in MATLAB SIMULINK software. The results proved that the V2G system can greatly improve the stability of system frequency.